2023
DOI: 10.1007/s13205-022-03446-2
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the stability of β-galactosidase immobilized onto soy-protein isolate-glutaraldehyde-functionalized carrageenan beads

Abstract: Uncontrolled enzyme-immobilizer interactions were evident after immobilizing β-galactosidase onto soy-protein isolate-glutaraldehyde-functionalized carrageenan beads. Such interactions triggered shortcomings in the immobilized β-galactosidase (iβGL) thermal and storage stabilities. The thermal stability of the iβGL was somewhat lesser than that of the free βGL. Moreover, the iβGL suffered an initial sharp fall-off in its activity after storing it. Thus, approaches were adopted to prevent the occurrence of such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…8,9 Also, linking all multimeric enzyme subunits to an immobilizer (easily obtained in the case of dimeric enzymes) will prevent their dissociation and prevent their inactivation. 8,9 The immobilization strategy facilitates the separation and reuse of the enzyme, thereby minimizing or eliminating protein contamination in the reaction medium, which significantly reduces the cost, thus ensuring its continued industrial applicability. 3 This article is licensed under CC-BY 4 Another benefit of utilizing an immobilized enzyme is that it avoids product contamination by the enzyme, which can be very undesirable especially in food technology.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…8,9 Also, linking all multimeric enzyme subunits to an immobilizer (easily obtained in the case of dimeric enzymes) will prevent their dissociation and prevent their inactivation. 8,9 The immobilization strategy facilitates the separation and reuse of the enzyme, thereby minimizing or eliminating protein contamination in the reaction medium, which significantly reduces the cost, thus ensuring its continued industrial applicability. 3 This article is licensed under CC-BY 4 Another benefit of utilizing an immobilized enzyme is that it avoids product contamination by the enzyme, which can be very undesirable especially in food technology.…”
Section: Introductionmentioning
confidence: 99%
“…Disruptions caused by immobilization can increase K i (inhibitory constant) to a greater extent than K m (Michaelis−Menten constant), reducing the effect of inhibition on the enzymatic reaction. 9 According to Garcia-Galan et al, 11 immobilization on a solid immobilizer may also lead to blockage of the enzyme inhibition zone and completely prevent this inhibition. Although immobilization has in many cases been associated with a decrease in enzyme activity or worsening of other catalytic properties, some reports in the literature have reported that immobilization of an enzyme also increases its activity (reaction rate per milligram of enzyme).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations